Transcriptional control of ovarian development in somatic cells - Ottolenghi, Chris; Colombino, Maria; Crisponi, Laura; Cao, Antonio; Forabosco, Antonino; Schlessinger, David; Uda, Manuela (Seminars in reproductive medicine, 2007)
Developmental transitions of the bipotential gonad to the embryonic ovary and thence to the follicle-filled mature ovary are expected to be coordinated by sets of transcription factors. We infer candidate lists here, focusing on somatic cell fate and function. For the mouse, developmental stages of ovary differentiation are relatively discretely phased, and provide a unique tool to investigate the intricate mechanisms that lead to the acquisition of female reproductive competence. Cross-platform gene expression profiles supplement functional studies of specific genes and comparative information about human biology. Available data suggest that: (1) peak transcription activity just precedes the two most decisive steps of early ovary differentiation (i.e., entry into meiosis and follicle formation); (2) alternating peak gene activities in oocytes and somatic cells may reflect reciprocal interactions; and (3) in addition to stable states of chromatin modification associated with morphogenesis, some features of differentiation are labile, contingent on the expression state of critical factors. Examples are the maintenance of somatic sex determination by continued Foxl2 action and the reversible maintenance of follicles in a quiescent state by nuclear Foxo3.